The effect of Leonurus cardiaca herb extract and some of its flavonoids on mitochondrial oxidative phosphorylation in the heart - Bernatoniene, Jurga; Kopustinskiene, Dalia M; Jakstas, Valdas; Majiene, Daiva; Baniene, Rasa; Kuršvietiene, Lolita; Masteikova, Ruta; Savickas, Arunas; Toleikis, Adolfas; Trumbeckaite, Sonata (Planta medica, 2014)
Motherwort (Leonurus cardiaca) possesses antibacterial, antioxidant, anti-inflammatory, and analgesic activities, and is used as a complementary remedy to improve heart function and blood circulation. Since cardiovascular diseases are often associated with an alteration of mitochondria, the main producers of ATP in cardiac muscle cells, the aim of our work was to determine bioactive constituents present in motherwort aerial parts extract in ethanol and investigate their effects on the functions of cardiac mitochondria. Quantitative determination of polyphenols in L. cardiaca herb extract was performed by HPLC. Mitochondrial respiration rates were evaluated using a Clark-type oxygen electrode. Mitochondrial ROS generation was determined fluorimetrically with Amplex Red and horseradish peroxidase. The results showed that constituents (chlorogenic acid, orientin, quercetin, hyperoside, and rutin) of L. cardiaca herb extract uncouple (by 20-90 %) mitochondrial oxidation from phosphorylation, partially inhibit (by ~ 40 %) the mitochondrial respiratory chain in cases of pyruvate and malate as well as succinate oxidation, and effectively attenuate the generation of free radicals in mitochondria. Since partial uncoupling of mitochondria, respiratory inhibition, and decreased ROS production are proposed as possible mechanisms of cardioprotection, our results imply that L. cardiaca herb extract could be a useful remedy to protect cardiac muscles from the effects of pathogenic processes.
Keywords: Mitochondria, Heart; Myocytes, Cardiac; kardiomyocyty; oxidativní fosforylace; Male; Antioxidants; Plant Extracts; Hydrogen Peroxide; Rats; Plant Components, Aerial; Cell Respiration; potkani Wistar; rostlinné extrakty; Flavonoids; Animals; flavonoidy; srdeční mitochondrie; buněčné dýchání; peroxid vodíku; antioxidancia; léčivé rostliny; zvířata; polyfenoly; Leonurus; nadzemní části rostlin; mužské pohlaví; krysa rodu Rattus; Rats, Wistar; Polyphenols; Oxidative Phosphorylation; Plants, Medicinal; srdečník